Bacterial community composition in the salivary glands of triatomines (Hemiptera: Reduviidae) - Lima, Michele Souza; Laport, Marinella Silva; Lorosa, Elias Seixas; Jurberg, José; dos Santos, Kátia Regina Netto; da Silva Neto, Mário Alberto Cardoso; Rachid, Caio Tavora Coelho da Costa; Atella, Georgia Correa (PLOS Neglected Tropical Diseases, 2018)
Author summary Chagas disease is caused by the parasite Trypanosoma cruzi and is transmitted through triatomines (Hemiptera: Reduviidae). It is estimated that over 10 000 people die every year from clinical manifestations of Chagas disease, and more than 25 million people risk acquiring the disease per year. Vector control remains the most effective method to prevent infection. In previous studies, the microbiota affected vector competence, thereby highlighting its potential for vector control. In this study, we demonstrate the presence of cultivable and non-cultivable bacteria in the salivary glands of different species of triatomines. The predominant bacterial genera appear to be specific to certain triatomines, e.g., the operational taxonomic units belonging to Arsenophonus bacterial genus is associated with the Triatoma spp, while these units belonging to unclassified Enterobacteriaceae bacterial family are associated with the Rhodnius spp. The operational taxonomic units found in low relative abundance also varied between species of triatomines and their occurrence could be influenced by the environment in which insects reside as well as inter-bacterial modulation by species-specific manner.